1988
DOI: 10.1111/j.1476-5381.1988.tb11647.x
|View full text |Cite
|
Sign up to set email alerts
|

Dicyclomine discriminates between M1‐ and M2‐muscarinic receptors in the guinea‐pig ileum

Abstract: 1 The affinity of the antagonist dicyclomine for subtypes of muscarinic receptors has been assessed in the myenteric plexus-longitudinal muscle preparation of the guinea-pig.2 Dicyclomine had a high affinity (pA2 9.13) for the neuronal MI-receptor whose activation by pilocarpine causes an increase in acetylcholine release. Dicyclomine had a low affinity for both the prejunctional M2-receptor (pA2 7.61) mediating inhibition of the electrically-evoked acetylcholine release and the postjunctional M2-receptor (pA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The evoked ACh release was also reduced by bethanechol (1-3 p M ) , a cholinomimetic drug (Fig. 2C), a result implying that the reduction is mediated via presynaptic muscarinic receptors (Kilbinger and Stein, 1988).…”
Section: S-3mentioning
confidence: 82%
“…The evoked ACh release was also reduced by bethanechol (1-3 p M ) , a cholinomimetic drug (Fig. 2C), a result implying that the reduction is mediated via presynaptic muscarinic receptors (Kilbinger and Stein, 1988).…”
Section: S-3mentioning
confidence: 82%
“…Together, these findings suggest that decreasing the activity through the muscarinic M1 receptors might modulate phenotypes in the Fmr1 KO mice. Studies using muscarinic antagonists have been hindered due to the lack of availability of good M1 antagonists that target the neuronal M1 receptors; however, dicyclomine, a selective muscarinic M1 antagonist, is reported to have ten times higher affinity for neuronal M1 receptors compared with the peripheral receptors (Giachetti et al 1986;Kilbinger and Stein 1988). In the current study, we evaluated the effects of decreasing M1 receptor activity on a number of behavioral responses in wild-type and Fmr1 KO mice following treatment with the M1 antagonist, dicyclomine.…”
Section: Introductionmentioning
confidence: 98%
“…Transmural stimulation of the guinea‐pig ileum has been demonstrated to release endogenous acetylcholine (Cowie et al ., 1978; Kilbinger, 1982; Kilbinger et al ., 1984). Endogenous acetylcholine, like exogenous oxotremorine‐M, elicits a pertussis toxin‐insensitive contractile response (Tucker, 1984; Lux & Schulz, 1986) mediated by the muscarinic M 3 receptor (Kilbinger et al ., 1984; Kilbinger & Stein, 1988) under standard assay conditions. We have also shown that endogenous acetylcholine acts on muscarinic M 2 receptors when the cyclic AMP stimulating relaxant agents isoproterenol or forskolin are present (Sawyer & Ehlert, 1999) during transmural stimulation.…”
Section: Introductionmentioning
confidence: 99%